Innovation and Education - Bulent Tarman (Research in Social Sciences and Technology, 2016)
We are living in a world that is changing rapidly and becoming more globalized. Especially the changes in the areas of science, technology and economy are becoming effective in the areas like education and health that are closely related to human life. We are experiencing a quick process named "globalization" that changes economic, social and political structures of the world and that no one can predict the outcome. These changes create new opportunities while opening new challenging areas. In order for countries to compete with each other, they need to be creative in all areas and they also need to be reformist to cope with domestic, national and global problems. In this study, the innovations in the area of education throughout the world will be examined and the place of Turkey compared to other countries in educational innovations will be analyzed. Also the concept of "˜Charter Schools" as acceleration in educational innovation in the United State of America, who is the leader in terms of innovation in the World, will be analyzed. This study will also analyze the Charter Schools in the USA and discuss whether the concept can be implemented in Turkey and bring dynamism to education or increase the quality of education. While looking for the answers of these questions, the researcher conducted a literature review and also used the data he gathered while staying in the USA for nine years for pursuing his MA and PhD degrees.